FRI0517 ANTI-CARBAMYLATED PROTEINS ANTIBODIES INDUCE OSTEOCLASTOGENESIS. (June 2019) - Massaro, Laura; Colasanti, Tania; Spinelli, Francesca; Ceccarelli, Fulvia; Mancini, Riccardo; Pecani, Arbi; Cipriano, Enrica; Perricone, Carlo; Miranda, Francesca; Truglia, Simona; Natalucci, Francesco; Leopizzi, Martina; et al.
Abstract : Background: Post-translational-modifications (PTMs) are implicated in the pathogenesis of autoimmune diseases, leading to the break of self-tolerance, generation of new autoantigens and production of autoantibodies. Anti-citrullinated-proteins antibodies (ACPA) play a key role in the pathogenesis of rheumatoid arthritis (RA) and many evidences showed that they are related to bone loss in RA. Osteoclasts are the primary targets of ACPA in the joint site, displaying citrullinated antigens on their surface. Carbamylation is another PTM generating the production of anti-carbamylated proteins antibodies (anti-CarP), recently proposed as a new biomarker for RA. Anti-CarP have been also studied in patients with systemic lupus erythematosus (SLE) with predominant joint involvement, showing a prevalence of 46.1%. Moreover, in SLE patients these autoantibodies have been also associated to bone erosive damage. The pathogenic mechanism of these autoantibodies is not completely clarified so far. Objectives: The aim of the present study was to investigate the possible pathogenic role of anti-CarP in the induction of osteoclastogenesis. Methods: Peripheral blood mononuclear cells (PBMCs) were isolated from a buffy coat from healthy donors using a Ficoll Hypaque gradient. Cells were cultured for 14 days in α-MEM complete medium, supplemented with 25 ng/ml of macrophage-colony-stimulating-factor (MCSF) and 30 ng/ml of receptor activator of nuclear-factor-kappa-β-ligand (RANKL), for the differentiation of monocytes in osteoclasts. Simultaneously, PBMCs were co-cultured in presence of anti-carbamilated-vimentin autoantibodies (anti-Vim CarP) purified from sera of 3 patients with RA and 3 patients with SLE with a predominant joint involvement at 100 ng/ml and 1 μg/ml. As control, intravenous immunoglobulin (IVIg) were used at the same concentrations. After 14 days, osteoclast differentiation was evaluated by staining cells for tartrate-resistant acid phosphatase (TRAP), using leukocyte acid phosphatase kit. Results: Anti-VimCarP purified from RA patients at 100 ng/ml were able to increase the median number of osteoclasts per well significantly more than untreated and IVIg at 100 ng/ml and 1 μg/ml (P=0.0008; P=0.0009 and P=0.0009, respectively). The same results were observed treating cells with 1 μg/ml of anti-VimCarP from RA patients (P=0.0008, P=0.002 and P=0.002, respectively). Similarly, anti-VimCarP purified from SLE patients at 100 ng/ml significantly increased the median number of osteoclasts than untreated and IVIg at 100 ng/ml and 1 μg/ml (P=0.002, P=0.004 and P=0.003, respectively). Analogously, we observed similar results co-culturing cells with 1 μg/ml of anti-VimCarP from SLE patients (P=0.002, P=0.02 and P=0.006, respectively). Conclusion: For the first time, we demonstrated that anti-Vim CarP purified from RA and SLE patients are able to induce osteoclastogenesis, suggesting their potential role as a biomarker of joint erosiveness in these autoimmune diseases. Disclosure of Interests: Laura Massaro: None declared, Tania Colasanti: None declared, francesca spinelli: None declared, Fulvia Ceccarelli: None declared, Riccardo Mancini: None declared, Arbi Pecani: None declared, enrica cipriano: None declared, Carlo Perricone Speakers bureau: BMS; Lilly, Celgene, Sanofi, Francesca Miranda: None declared, Simona Truglia: None declared, Francesco Natalucci: None declared, Martina Leopizzi: None declared, Valeria Di Maio: None declared, Carlo Della Rocca: None declared, cristiano alessandri: None declared, Guido Valesini: None declared, fabrizio conti: None declared